Diboronate-Modified Hyaluronic Acid for Glucose-Responsive Insulin Delivery - Xian, Sijie; Xiang, Yuanhui; Mitrová, Katarína; Jiráček, Jiří; Webber, Matthew J (Biomacromolecules, 2025)
Diabetes requires precise insulin management to maintain glycemic control and prevent severe complications. Glucose-responsive delivery systems envision an autonomous approach to improve insulin therapy. Here, a glucose-sensitive insulin delivery system comprising hyaluronic acid conjugated with a diboronate glucose binder as a carrier for diol-modified insulin is shown. This approach seeks improved precision in insulin delivery, leveraging bidentate glucose binding to achieve enhanced glucose affinity and specificity. Modification of insulin with a diol motif preserves its native conformation and function. These insulin formulations correct blood glucose in diabetic mice, including glucose-responsive function when subjected to a glucose challenge. However, the absence of secondary interactions, such as electrostatic complexation, ultimately limits the duration of function relative to that of previous platforms. Integrating complementary interactions alongside dynamic-covalent glucose binders therefore enhances the functional duration and therapeutic efficacy in the design of glucose-responsive polymeric carriers, offering design insights into the development of new carriers for glucose-responsive insulin delivery.
Keywords: nosiče léků; Drug Carriers; glukosa; krevní glukóza; kyseliny boronové; inzulin; mužské pohlaví; Insulin; Mice; lékové transportní systémy; hypoglykemika; experimentální diabetes mellitus; Blood Glucose; kyselina hyaluronová; zvířata; Hyaluronic Acid; Diabetes Mellitus, Experimental; myši; Drug Delivery Systems; Hypoglycemic Agents; Boronic Acids; Glucose; Male; Animals